Esophageal Interventions in Infants Born with Esophageal Atresia: A Comprehensive Analysis of a National Database - König, Tatjana T.; Gianicolo, Emilio; Frankenbach, Luisa; Wittenmeier, Eva; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2021)
Introduction Esophageal atresia (EA) is a rare malformation that often requires a series of procedures, including surgical primary anastomosis, staged repair, and endoscopic procedures. Actual numbers and trends in interventions and variety in treatment strategies remain unclear.Materials and Methods Data from the German federal bureau of statistics containing all EA-related inpatient procedures encoded from 2005 until 2018 were analyzed for children during the first year of life. The sum of esophageal anastomoses and replacements was used to calculate an estimate of incidence of EA.Results Over 14 years, 12,627,888 inpatient cases were recorded in infants in Germany. The mean incidence of EA was 1 per 4,217 live births. On average, 163.3 (95% confidence interval [CI]: 150.8–176.1) esophageal anastomoses, 11.2 (95% CI: 8.7–13.7) esophageal lengthening procedures, and 6.7 (95% CI: 5.42–8.00) esophageal replacements were recorded annually. Overall, 187.8 (95% CI: 147.1–200.4) endoluminal treatments (ballon dilatation, bougienage, stent placement, or injection) were performed per 100 anastomoses. Over the years, bougienage was increasingly replaced by ballon dilatation as primary treatment. Boys had a significantly higher number of esophageal procedures than girls, but the incidence of endoscopic treatments in relation to anastomoses was the same for both genders.Conclusion The low incidence of EA in relation to a relatively large number of units treating those patients in Germany may pose challenges for maintaining competency and training of all specialists involved. The number of esophagoscopic treatments for esophageal stricture per anastomosis is lower than previously estimated.
Keywords: esophageal malformation; esophageal anastomosis; esophageal lengthening procedure; esophageal replacement; esophageal dilatation